Different methods for reproducing time, different results - Mioni, Giovanna (2014)
One of the most widely used tasks for investigating psychological time, time reproduction, requires from participants the reproduction of the duration of a previously presented stimulus. Although prior studies have investigated the effects of different cognitive processes on time reproduction performance, no studies have looked into the effects of different reproduction methods on these performances. In the present study, participants were randomly assigned to one of three reproduction methods, which included (a) just pressing at the end of the interval, (b) pressing to start and stop the interval, and (c) maintaining continuous pressing during the interval. The study revealed that the three reproduction methods were not equivalent, with the method involving keypresses to start and stop the reproduction showing the highest accuracy, and the method of continuous press generating less variability.